2022
DOI: 10.3390/nu14091703
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Individualized Nutritional Support for Hospitalized Patients with Chronic Heart Failure

Abstract: Background Malnutrition is a highly prevalent risk factor in hospitalized patients with chronic heart failure (CHF). A recent randomized trial found lower mortality and improved health outcomes when CHF patients with nutritional risk received individualized nutritional treatment. Objective To estimate the cost-effectiveness of individualized nutritional support in hospitalized patients with CHF. Methods This analysis used data from CHF patients at risk of malnutrition (N = 645) who were part of the Effect of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…As for all modeling analyses, our model had limitations as previously reported ( 10 , 11 ). Of note, the calculation of costs and cost savings was informed from the perspective of the Swiss hospitals included in the original EFFORT trial ( 29 ), which may not be representative of other hospitals worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for all modeling analyses, our model had limitations as previously reported ( 10 , 11 ). Of note, the calculation of costs and cost savings was informed from the perspective of the Swiss hospitals included in the original EFFORT trial ( 29 ), which may not be representative of other hospitals worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…The objective of our present analysis was to determine whether the recovery benefits of nutritional support were paralleled by cost-effectiveness of this nutritional care. For our current cost-effectiveness analysis, we examined hospital costs and health outcomes in patients with cancer, using modeling to compare results for the nutritional intervention and control groups, as we have done previously for poorly nourished medical inpatients ( 10 ) and for patients with chronic heart failure ( 11 ). We used clinical data of patients with cancer included in the EFFORT trial – the largest randomized trial today outside critical care that compared clinical outcomes among patients receiving individualized nutritional support with usual hospital care ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in terms of complications, patients receiving nutritional support had a cost savings of 6214 SF and an additional 4.11 life days without complications, with an incremental cost-effectiveness ratio for avoided complications of 1513 SF per life day gained. Thus, the economic analysis concluded that in-hospital nutritional support for chronic HF patients increased life expectancy at an acceptable incremental cost-effectiveness ratio [95].…”
Section: Artificial Nutritional Supportmentioning
confidence: 99%
“…Malnutrition is prevalent among patients with chronic heart failure (CHF) due to the lack of appetite, unintentional weight loss, impaired intestinal function, catabolic metabolism, and other comorbidities. Schuetz et al [13] investigated the cost-effectiveness of an individualised nutritional therapy in 645 hospitalised patients with CHF. The authors found that the overall incremental cost-effectiveness ratio for the individualised nutritional therapy vs. no nutritional therapy was 2625 Swiss Francs per life day gained.…”
Section: Infections Chronic Conditions Malnutrition and All-cause Mor...mentioning
confidence: 99%
“…The authors found that the overall incremental cost-effectiveness ratio for the individualised nutritional therapy vs. no nutritional therapy was 2625 Swiss Francs per life day gained. They concluded that the intervention increased life expectancy at an acceptable incremental cost-effectiveness ratio [13].…”
Section: Infections Chronic Conditions Malnutrition and All-cause Mor...mentioning
confidence: 99%